Surgical repair of esophageal atresia: do trans-anastomotic feeding tubes have an impact on the outcome? - Batikhe, Mohamed Yousef; Redwan, Mostafa; Gafar, Ahmed; Ramadan, Mohamed (Frontiers in Pediatrics, 2025)
IntroductionTransanastomotic feeding tubes (TATs) are placed to allow early feeding following esophageal atresia/tracheoesophageal fistula (EA/TEF) repair. However, recently these tubes were linked to increased rates of postoperative complications. The aim of this study is to report our single center experience with and without the use of TATs in patients with EA/TEF.Patients and methodsThe data of 152 patients operated for EA and distal TEF in our hospital from January 2014 to September 2024 were retrospectively reviewed. Patients were divided into two groups; those who did not have TATs (NOTAT group) and those who have their TATs left in-place until deliberately removed according to postoperative care protocol (TAT group). Both groups were compared regarding baseline characteristics, operative findings, postoperative care and postoperative complications.ResultsThe TAT group included 130 patients while the NOTAT group included 22 patients. There were no statistically significant differences between the two groups in terms of birth weight, gestational age, the rate of prematurity or the associated anomalies. The time of commencing enteral feeding was significantly earlier in the TAT group (median POD #3 vs. POD# 13 in the NOTAT group) and the duration of TPN was significantly shorter (mean of 6.6 vs. 16.2 days in the NOTAT group). There were no statistically significant differences between the two groups regarding the rate of postoperative anastomotic leaks (23.0% in the TAT group vs. 18.1% in the NOTAT group; p = 0.700) or strictures.ConclusionTrans anastomotic feeding tubes (TATs) offer benefits in terms of early enteral feeding, and shorter duration of parenteral nutrition for patients with EA/TEF undergoing surgical repair. At the same time, they don't seem to add a risk of anastomotic leaks or strictures. Large prospective randomized studies are required to further evaluate any possible relationships between TATs and the postoperative complications following repair of EA/TEF.